PENGARUH MEDIUM PERENDAM TERHADAP SIFAT MEKANIK, MORFOLOGI, DAN KINERJA MEMBRAN NATA DE COCO - Senny Widyaningsih; Hartiwi Diastuti (Universitas Jenderal Soedirman, 2008)
Nata de coco is bacterial cellulose which is produced by Acetobacter xylinum in fermentation process of coconut water. Based on its properties, nata de coco can be used as a membrane. Soaking medium in purification of nata de coco gel can influence structure, morphology, and performance of nata de coco membrane. First medium was NaOCl 0.05% and NaOH 5%, Second medium was ultrasonic. Third medium was NaOH 1% and CH3COOH 1%. Mechanical property were analysized based on its tensile strength. Morphology of membrane was analysized using SEM. Performance of membrane was determined based on its permeability. The result showed that nata de coco membrane which had the best value on mechanical properties, morphology, and performance was membrane in third medium.